Impact of lockdown and school closure on children's health and well-being during the first wave of COVID-19: a narrative review - BORAN, PERRAN (BMJ PUBLISHING GROUP, 2021)
Background In the context of containment measures against the COVID-19 pandemic, the aims were to examine the impact of lockdown and school closures on childs' and adolescents' health and well-being and social inequalities in health. Methods Literature review by searching five databases until November 2020. We included quantitative peer-reviewed studies reporting health and well-being outcomes in children (0-18 years) related to closure measures' impact due to COVID-19. A pair of authors assessed the risk of bias of included studies. A descriptive and narrative synthesis was carried out. Findings Twenty-two studies, including high-income, middle-income and low-income countries, fulfilled our search criteria and were judged not to have an increased risk of bias. Studies from Australia, Spain and China showed an increase in depressive symptoms and decrease in life satisfaction. A decrease in physical activity and increase in unhealthy food consumption were shown in studies from two countries. There was a decrease in the number of visits to the emergency department in four countries, an increase in child mortality in Cameroon and a decrease by over 50% of immunisations administered in Pakistan. A significant drop of 39% in child protection medical examination referrals during 2020 compared with the previous years was found in the UK, a decrease in allegations of child abuse and neglect by almost one-third due to school closures in Florida, and an increase in the number of children with physical child abuse trauma was found in one centre in the USA. Interpretation From available reports, pandemic school closure and lockdown have adverse effects on child health and well-being in the short and probably long term. We urge governments to take the negative public health consequences into account before adopting restrictive measures in childhood.
Keywords: adolescents; children health; COVID-19; lockdown; school closure; social inequalities; ADOLESCENTS